High-Throughput flaA Short Variable Region Sequencing to Assess Campylobacter Diversity in Fecal Samples From Birds - Zhang, Qian; Al-Ghalith, Gabriel A.; Kobayashi, Mayumi; Segawa, Takahiro; Maeda, Mitsuto; Okabe, Satoshi; Knights, Dan; Ishii, Satoshi (Frontiers in Microbiology, 2018)
Current approach to identify sources of human pathogens is largely dependent on the cultivation and isolation of target bacteria. For rapid pathogen source identification, culture-independent strain typing method is necessary. In this study, we designed new primer set that broadly covers flaA short variable region (SVR) of various Campylobacter species, and applied the flaA SVR sequencing method to examine the diversity of Campylobacter spp. in geese fecal samples with and without bacteria cultivation. We also developed and optimized the sequence data analysis pipeline to identify as many genotypes as possible, while minimizing the detection of genotypes generated by sequencing errors. Our results suggest that the flaA SVR sequencing can cluster Campylobacter strains with higher discriminant power than conventional flaA restriction fragment length polymorphism (RFLP) method. Culture-independent flaA SVR MiSeq sequencing identified almost all flaA genotypes obtained by culture-based method. In addition, more flaA genotypes were identified probably due to high throughput nature of the MiSeq sequencing. These results suggest that the flaA SVR sequencing could be used to analyze the diversity of Campylobacter spp. without bacteria isolation. This method is promising to rapidly identify potential sources of Campylobacter pathogens.